Forming Ecological Citizenship Attitudes in Aquatic Environment Schools - Dian Agus Ruchliyadi; Rabiatul Adawiah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The discourse surrounding environmental issues in Indonesia has been ongoing for a considerable duration. However, the endeavours undertaken by various segments of society, such as the environmental activist community or the promotion of environmental awareness in schools, have not yet reached their full potential.   The aim of this study was to examine the techniques implemented by schools, particularly those located near the Banjarmasin City River, in order to cultivate an ecological civic mindset.   This study utilises a qualitative research approach.   Data collecting encompassed the utilisation of interviews, questionnaires, observation, and documentation. The obtained data were analyzed using techniques for interactive model analysis. This study was conducted at Public Elementary Schools and State Junior High Schools in Banjarmasin City that are close to the river. The results of this study indicate that the ecological citizenship of students in the city of Banjarmasin at the elementary school level is very good 9%, good 54%, bad 36%, and very bad 1%. For junior high school level are: very good 1%, good 39%, bad 36% and very bad 24%. The role of schools in forming ecological citizenship, namely: teachers and education staff become examples for students, carrying out Clean Friday and Healthy Friday programs every week that all school members must follow; integrating through fields of study, asking students to check the cleanliness of the classroom before learning begins, requiring traders in the school environment to provide paper or leaf wrappers, collaborating with the Forest Community Forum (FKH) and giving appreciation to students by selecting cleanliness ambassadors every year.